Relationships of Urinary Beta2- microglobulin in Neonates with Impaired Renal Function in Different Stages of Hypoxic Ischaemic Encephalopathy (Bangladesh Journal of Child Health, 2013)
Hypoxic Ischaemic Encephalopathy (HIE) is a sequelae of neonates suffering from severe perinatal asphyxia. It may also cause impaired renal function due to acute tubular necrosis followed by elevation of urinary concentration of certain low molecular weight proteins like ?2- microglobulin. This study was designed to evaluate the urinary ?2- microglobulin level in neonates with HIE patients those who have impaired renal function. This prospective case control study was carried out in the Neonatal unit of the department of Pediatrics and in the Labor ward of the department of Obstetrics and Gynecology Bangabandhu Sheik Mujib Medical University, Dhaka during the period of 1st July 2005 to 30th June 2006. This study was designed to estimate urinary ?2- micro globulin level in the asphyxiated newborn as well normal newborns to see any significant changes and to find out its relation with over all outcomes of newborns with perinatal asphyxia. In this study, 42 term newborn babies before 24 hours of age, those who failed to take spontaneous breathing within 5 minutes of the complete delivery were taken as cases and 40 healthy term newborns were taken as control. Asphyxiated newborns were divided into three groups depending on the sarnat and sarnat clinical staging of HIE. Mean±SD value of urinary ?-2- micro globulin in case group 4.1 ± 2.79 mg/l and in the control was 1.35 ± 1.08 mg/l. It shows significant (p